AOT/isooctane reverse micelles with a microaqueous core act as protective shells for enhancing the thermal stability of Chromobacterium viscosum lipase. (15th July 2015) - Hong, Sung-Chul; Park, Kyung-Min; Son, Young-Hwan; Jung, Ho-Sup; Kim, Keesung; Choi, Seung Jun; Chang, Pahn-Shick
Highlights: Thermostability of Chromobacterium viscosum lipase in reverse micelles was investigated. Enzyme-deactivation kinetics corresponded with two-step series-type deactivation model. The deactivation constants decreased when the lipase was entrapped in reverse micelles. The R value ([water]/[surfactant]) of reverse micelles influenced the thermostability. The tryptophyl contribution increased during the thermal-treatment in aqueous buffer. Abstract: According to the different environmental systems for lipase reactions, changes in thermal stability were investigated by employing the Chromobacterium viscosum lipase and a two-step series-type deactivation model. The half-life (6.81 h) of the lipase entrapped in reverse micelles at 70 °C was 9.87- and 14.80-fold longer than that in glycerol pool or in aqueous buffer. The deactivation constants for the first and second step ( k 1 and k 2 ) at all temperatures drastically decreased when the lipase was entrapped in reverse micelles. In particular, k 1 (3.84 h −1 ) at 70 °C in reverse micelles was 1.57-fold lower than that in aqueous buffer (6.03 h −1 ). Based on the fluorescence spectrometry, the amount of excited forms of tryptophan and tyrosine increased markedly during the thermal-treatment in aqueous buffer, whereas no significant fluctuation was noted in the reversed micellar system. These results indicated that the encapsulation in reverse micelles could be favorable for preventing the enzyme from heat-induced denaturation.